On Gamification and Students’ Reading Ability in Vocational High School - Rita M Siregar; Kisno Kisno; Sherly Sherly; Tiodor Sri Manalu (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2023)
Network connectivity, communication interaction, and technology enjoyment are the consumption of the digital generation.The application of learning media is interesting in the world of educational teaching especially in teaching reading. The objective of this research is to investigate the effect of gamification on students' reading ability. This research implemented quasi-experiment method with pre-test and post-test nonequivalent group design. In the experimental class, the students were taught using the gamification, while the control class was by conventional method. The researchers used cluster sampling where 24 students became the sample in experiment class and 12 students in control class respectively. The pretest and posttest were used as an instrument to collect data and the test scores were analyzed using IBM SPSS Statistics 20. The results of independent t test showed the (3.334 > 1.694) and the average reading ability value of students taught using the gamification increased significantly. Therefore, gamification was recommended as one of the interesting efficient learning media in rectifying students' reading ability